Избранное: поэзия / А. Д. Дементьев - Дементьев А. Д. (Золотая серия поэзии, 2009)
Экземпляры: (20191014) / Инвентарный номер: 34602 / Цена: 110.00 / Сис.шифр: Р2 / Авт.знак: Д 30 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6